Metaphorical Expressions in the Uzbek Language and Their Communicative Functions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This study investigates metaphorical expressions in the Uzbek language and explores their communicative functions in everyday speech, literature, and media. Metaphors serve not only as stylistic devices but also as cognitive and cultural tools, enabling speakers to convey abstract ideas, emotions, and social values effectively. The research provides a theoretical framework for understanding metaphors, classifies their types, and analyzes their role in facilitating communication, enriching stylistic expression, and reflecting cultural identity. Examples from contemporary Uzbek language and literature illustrate the multifunctional nature of metaphors. The study emphasizes the importance of integrating metaphor analysis into language education, translation practices, and intercultural communication to enhance comprehension and preserve linguistic richness.